PELAKSANAAN ASSESMENT OLEH POLRES KEPULAUAN MENTAWAI SEBAGAI BENTUK PELAKSANAAN REHABILITASI BAGI PECANDU DAN KORBAN PENYALAHGUNAAN NARKOTIKA - Simbolon, Laurensius Arliman (Jurnal Muhakkamah, 2020)
The Assessment Process is an initial stage where narcotics addicts and victims of narcotics abuse report to the National Narcotics Agency requesting rehabilitation. This process can be used as a benchmark for drug addicts and victims of narcotics abuse itself to determine the length of the rehabilitation period for narcotics addicts and victims of narcotics abuse who request to be rehabilitated. From the results of the assessment it was also used as material for consideration of the Integrated Assessment Team in making decisions on the application. Today, based on data from the National Narcotics Agency (BNNP) of West Sumatra Province, the problem of abuse of current drug abuse in the Mentawai is very alarming. This research is a descriptive analytical study. The approach used in this study is a normative juridical approach supported by an empirical juridical approach. The process of implementing rehabilitation for addicts and victims of narcotics abuse by the Mentawai Islands Police Satnarkoba has been running in accordance with Law No. 35 of 2009. However, there is a possibility that there are always shortcomings in carrying out these rules. The obstacle of police investigators in determining rehabilitation for drug users is the lack of awareness or willingness of narcotics abusers who are old enough to report themselves to the police to be directed to IPWL or reported by families if narcotics users are not old enough, fearing that parents or families of narcotics users will be damaged their image if it is known that the child or family member is a drug user so that they are reluctant to report themselves, there are still many people who do not know that rehabilitation for drug users is all costs borne by the government / free.